Bem-estar financeiro e Psicologia Clínica: em busca de um caminho sustentável - Toyama, Rebeca de Souza Cordeiro (2022)
Difficulties about money issues are frequent. In my work, dealing with career planning, I realize this fact, where financial concerns are related as the main cause for the gap between career and purpose. The implications of indebtedness, default, bankruptcy and other problems go beyond the career. They influence people's mental and physical health. In the socioeconomic global field, with changes in labor relations, increased longevity, added to the SARS COV-II (COVID-19) pandemic, issues related to financial well-being (FWB) are gaining importance in society. At the same time, professionals from different areas such as educators, managers, economists, lawyers and psychologists, could contribute with more specific knowledge on this subject related to their expertise field. They care about some lack of knowledge, not provided during their professional qualification at college. This study aimed to investigate what has already been produced on FWB, psychology and sustainability in Brazil, through an integrative review, by the articulation between FWB, psychology and sustainability, in order to identify FWB contributions in the Clinical Psychology context in sustainability pursuit. The bibliographic survey took place in the Federated Academic Community (CAFe), at the collection of the CAPES Periodicals Portal and Google Scholar. To be included, articles should be peer-reviewed and written in Portuguese, published between January 2015 and January 2022. Articles written in other languages, research whose focus is not Brazil and articles that consider the FWB of companies were excluded. The specific objectives are to identify research in Psychology that has the FWB as an objective; search the existence of studies on FWB focused on sustainability and to propose study contributions on FWB in the Clinical Psychology context. 52 articles were found. Considering English written articles, the result achieved a 7,937 papers amount, what seems to corroborate this research`s importance. From the 52 articles, 16 were selected, where only 1 came from a Psychology journal. The greatest concentration was in Administration. The North Region presented the smallest sampling. Rio Grande do Sul had the largest number of publications, as it is the area of activity of the Administration researchers, Vieira and Campara, authors who have the largest number of selected articles. Financial education, financial literacy and FWB were the most found keywords. There was no significant difference between the number of qualitative and quantitative surveys. No sustainability focused paper was found in Clinical Psychology or FWB. The frequent use of Psychology content in FWB research may suppose the relevance and turn into opportunity for Psychology´s future findings. This study results confirm some possibilities about interdisciplinary interactions, a clear finding that seems occur when approaching Administration, an applied social science, with Psychology, a science of human essence. This research was made possible with the “National Council for Scientific and Technological Development – (CNPq) – Brazil” support